Effects of bariatric surgery on renal function: a retrospective cohort study comparing one-year outcomes between one-anastomosis gastric bypass and Roux-en-Y gastric bypass - Ivano, Victor Kenzo; Hatto, Marcelo; Teramoto, Fernanda; Macedo, Paolla Ravida Alves de; Gestic, Martinho Antonio; Utrini, Murillo Pimentel; Chaim, Felipe David Mendonça; Ramos, Almino Cardoso; Callejas Neto, Francisco; Chaim, Elinton Adami; Cazzo, Everton (São Paulo Medical Journal, 2025)
BACKGROUND: Evidence on the effect of one-anastomosis gastric bypass (OAGB) on renal function is limited. OBJECTIVE: To compare the evolution of estimated renal function observed 1 year after OAGB and Rouxen-Y gastric bypass (RYGB) in individuals with obesity. DESIGN AND SETTING: Observational, analytical, and retrospective cohort study. Tertiary-level university hospital. METHODS: This study used a prospectively collected database of individuals who consecutively underwent bariatric surgery. Renal function was assessed by calculating the estimated glomerular filtration rate (eGFR), according to the Chronic Kidney Disease Epidemiology Collaboration. The one-year variation in the eGFR was compared between the procedures. RESULTS: No significant differences in age, sex, obesity-associated conditions, or body mass index were observed among individuals who underwent either OAGB or RYGB. OAGB led to a significantly higher percentage of total (P = 0.007) and excess weight loss (P = 0.026). Both OAGB and RYGB led to significantly higher values of eGFR (103.9 ± 22 versus 116.1 ± 13.3; P = 0.007, and 102.4 ± 19 versus 113.2 ± 13.3;P < 0.001, respectively). The one-year variation in eGFR was 11 ± 16.2% after OAGB and 16.7 ± 26.3% after RYGB (P = 0.3). Younger age and lower baseline eGFR were independently associated with greater postoperative improvement in renal function (P < 0.001).CONCLUSION: Compared with RYGB, OAGB led to an equivalent improvement in renal function 1 year after the procedure, along with greater weight loss.